FACTORS THAT AFFECT THE REMAINING BUSINESS RESULTS IN COOPERATIVES (Study On Kpri Cooperatives Of Sincere Teachers Kuok 2016-2018) - Arisman Arisman; Arman Arman; Mustafa Kamal (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to find out the influence of outside capital, own capital, number of members and operational costs simultaneously and partially on shu kpri cooperative GGIK Kuok. The data used in this study is secondary data in the form of monthly report data for the period 2016-2018. The data is processed with multiple linear regression analysis techniques. The test results showed that outside capital, own capital, number of members and operational costs had a significant effect simultaneously on shu. The results of partial testing of own capital, number of members, operational costs significantly affected the SHU while outside capital had no significant effect on the KPRI Cooperative SHU GGIK Kuok. The density of the free variable relationship to the free variable is very strong, the large coefficient of free variables against variables is bound to 98%.